From Registers to Reflections on the Body in Process of Creation - Ribeiro, Mônica Medeiros (Revista Brasileira de Estudos da Presença, 2020)
The article presents a reflection on the body through the study of movement registers in the creation process of the show Aldebaran, by Grupo Oficcina Multimédia. Considering the body as the focus, an inventive observation, corporeal reading of movement drawings and a literature review were undertaken. Movement registers are discussed as performative mnemonic instances that enable corporeal resonances between the scholar of the process and the images of the movements. The body in resonance is shown as a condition for poetic interactions in scene constitution in dance and theater, and resonance is considered as a corporeal operator of artistic fruition and alterity practices.